HELLS Is negatively regulated by wild-type P53 in liver cancer by a mechanism involving P21 and FOXM1 - Schüller, Stefanie; Sieker, Jan; Riemenschneider, Philip; Köhler, Bianca; Drucker, Elisabeth; Weiler, Sofia Maria Elisabeth; Dauch, Daniel; Sticht, Carsten; Goeppert, Benjamin; Rössler, Stephanie; Ribback, Silvia; Breuhahn, Kai; et al. (Cancers, 2022)
The major tumor suppressor P53 (TP53) acts primarily as a transcription factor by activating or repressing subsets of its numerous target genes, resulting in different cellular outcomes (e.g., cell cycle arrest, apoptosis and senescence). P53-dependent gene regulation is linked to several aspects of chromatin remodeling; however, regulation of chromatin-modifying enzymes by P53 is poorly understood in hepatocarcinogenesis. Herein, we identified Helicase, lymphoid specific (HELLS), a major epigenetic regulator in liver cancer, as a strong and selective P53 repression target within the SNF2-like helicase family. The underlying regulatory mechanism involved P53-dependent induction of P21 (CDKN1A), leading to repression of Forkhead Box Protein M1 (FOXM1) that in turn resulted in downregulation of HELLS expression. Supporting our in vitro data, we found higher expression of HELLS in murine HCCs arising in a Trp53−/− background compared to Trp53+/+ HCCs as well as a strong and highly significant correlation between HELLS and FOXM1 expression in different HCC patient cohorts. Our data suggest that functional or mutational inactivation of P53 substantially contributes to overexpression of HELLS in HCC patients and indicates a previously unstudied aspect of P53′s ability to suppress liver cancer formation.